(untitled) (Repertorio Científico, 2024)
GeoGebra is an open-source mathematical software that offers educators the possibility to create attractive educational materials to facilitate the understanding of complex mathematical concepts. The objective of this workshop is to train participants in the use of GeoGebra as a tool for creating interactive presentations that combine graphical, numerical, algebraic, and other elements; these elements allow the inclusion of developed exercises and theory, among other resources that enrich educational resources in the context of distance education. In this workshop, an expository methodology is used, which provides active participation from the workshop participants. The facilitator presents and explains the most relevant tools, such as sliders, which allow you to create a navigation bar, Boolean conditions, and check boxes to show or hide objects, among other outstanding features of GeoGebra. The workshop is framed under the thematic axis Pedagogical mediation in educational resources for a distance education model and intends that the participant develop a material for the approach to the thematic content: systems of linear equations with two unknowns. The material developed allows for mediation of said content, providing students with the opportunity to reinforce mathematical concepts effectively. As a result, participants will have achieved not only a dynamic presentation, but also a methodology for the effective use of GeoGebra in distance pedagogical mediation